Exploring pain management in breast cancer: key findings from the ARISE study - Donati, Costanza M.; Zamagni, Alice; Zamfir, Arina A.; Aristei, Cynthia; Cammelli, Silvia; Zamagni, Claudio; Paolinelli, Silvia; Buwenge, Milly; Rossi, Romina; Maltoni, Marco; Morganti, Alessio G.; Cilla, Savino (Frontiers in Oncology, 2025)
AimsThis ARISE study secondary analysis aims to delve into the complexities of pain management in breast cancer patients undergoing radiotherapy (RT) in Italy. It aims to identify and analyze predictive variables for pain management adequacy and establish the relationship between these variables and the effectiveness of pain control.Materials and methodsThis observational study engaged 2,104 participants from 13 Italian RT departments, focusing on 426 breast cancer patients reporting pain. Advanced statistical methods, were employed to identify significant predictive variables for pain management adequacy. Data collection involved a standardized form capturing personal, health-related information, specifics about cancer, pain intensity, and medication. The Pain Management Index (PMI) was used to evaluate pain management adequacy, where negative PMI values indicate inadequate or suboptimal pain management.ResultsThe analysis showed that 61.7% of patients experienced inadequate pain management (PMI<0). Factors identified as influencing pain management adequacy included the type of pain, patient age, the objective of RT, and the geographical location of the RT center. Notably, patients undergoing curative RT exhibited a higher incidence of inadequate pain management (PMI<0) compared to those undergoing palliative RT (82.9% versus 31.4%). Geographical variations were evident, with patients treated in northern Italy showing better pain management compared to those in central-southern Italy (72.0% versus 85.6%).ConclusionThe ARISE study underscores a significant inadequacy in pain management among breast cancer patients undergoing RT in Italy, influenced by a complex interplay of treatment-related, demographic, and regional factors. The study findings emphasize the need for enhanced, personalized pain management strategies and highlight the importance of considering a multifaceted approach.